53.6k views
4 votes
Given the recursive formula for an arithmetic sequence find the common difference and the 52nd term

Given the recursive formula for an arithmetic sequence find the common difference-example-1

1 Answer

3 votes

Answer:

Common difference(d)
a_(52)

(21) -10 -548

(22) -7 -323

(23) 10 547

(24) -100 -5118

Explanation:

Let the common difference be denoted by 'd'.

Also the nth difference of an arithmetic sequence is given by:
a_(n)=a_(1)+(n-1)* d

(21)

We are given a recursive formula as:


a_(n)=a_(n-1)-10

The first term is given by:


a_(1)=-38

The common difference for an arithmetic sequence is given by:


a_(n)-a_(n-1)

Hence, here we have the common difference as:


d=-10

The nth term of an arithmetic sequence is given by:


a_(n)=a_(1)+(n-1)* d

Here
a_(1)=-38 and
d=-10.

Hence,
a_(52)=-38+(52-1)* (-10)

Hence,
a_(52)=-548

(22)


a_(n)=a_(n-1)-7


a_(1)=34

The common difference for an arithmetic sequence is given by:


a_(n)-a_(n-1)

Hence, here we have the common difference as:


d=-7

Here
a_(1)=34 and
d=-7.

Hence,
a_(52)=34+(52-1)* (-7)

Hence,
a_(52)=-323

(23)


a_(n)=a_(n-1)+10


a_(1)=37

The common difference for an arithmetic sequence is given by:


a_(n)-a_(n-1)

Hence, here we have the common difference as:


d=10

Here
a_(1)=37 and
d=10.

Hence,
a_(52)=37+(52-1)* (10)

Hence,
a_(52)=547

(24)


a_(n)=a_(n-1)-100


a_(1)=-18

The common difference for an arithmetic sequence is given by:


a_(n)-a_(n-1)

Hence, here we have the common difference as:


d=-100

Here
a_(1)=-18 and
d=-100.

Hence,
a_(52)=-18+(52-1)* (-100)

Hence,
a_(52)=-5118


User Cristian Hantig
by
5.6k points